2016
DOI: 10.1038/icb.2016.84
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage polarization and MRSA infection in burned mice

Abstract: Mortality associated with Staphylococcus aureus infection remains high during the sub-acute phase of burn injury. In this study, we aimed to improve antibacterial resistance of sub-acutely burned mice through macrophage polarization. Sepsis did not develop in mice at the sub-acute phase of 5% total body surface area (TBSA) burn after being infected with methicillin-resistant S. aureus (MRSA), and M1 macrophages (interleukin (IL)-10IL-12 inducible nitric oxide synthase Mφ) were isolated from these mice. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Interestingly, CCL1 released from M2b cells is essentially required for maintaining the properties of M2b monocytes/macrophages . Growing evidences have shown that CCL1 is the specific molecular identifier of M2b and may serve as a marker for identifying M2b from the other subtypes of macrophages …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, CCL1 released from M2b cells is essentially required for maintaining the properties of M2b monocytes/macrophages . Growing evidences have shown that CCL1 is the specific molecular identifier of M2b and may serve as a marker for identifying M2b from the other subtypes of macrophages …”
Section: Phenotypic Markers Of M2bmentioning
confidence: 99%
“…Under normal physiologic conditions, monocytes in the blood retain a quiescent state (M0: CCL1 − , CD163 − , CD14 + ) . During infection, monocytes/macrophages acquire the M1 phenotype (IL‐10 − , IL‐12 + , iNOS + , CXCL9 + ), which is a major effector cells for the first line of host antibacterial defense . Mild burn injury (5% of the total body surface area [TBSA] burn) induces M1 macrophage polarization .…”
Section: M2b Macrophages and Diseasesmentioning
confidence: 99%
See 3 more Smart Citations